Missing Intrauterine Device Copper-T: Case Series - Thapa, Shekhar; Dangal, Ganesh; Karki, Aruna; Pradhan, Hema Kumari; Shrestha, Ranjana; Bhattachan, Kabin; Pokharel, Shreesiya; Paudel, Rekha; Bajracharya, Nishma (Journal of Nepal Health Research Council, 2018)
An intrauterine contraceptive device (IUD) is a long acting, highly effective, economic and reversible method of contraception used worldwide. The most used devices are copper IUD (Copper-T) or Progesterone IUD. Common complications include failed insertion, pain, vasovagal reactions, infection, menstrual abnormalities, expulsion and rarely uterine embedment and perforation. In this case series we will discuss three cases of missing Copper-T. In one case Copper T was inserted at our hospital and in the other cases it was inserted in the periphery and all the cases was managed surgically with different modality. Keywords: Copper-T; Intrauterine device; laparoscopy; laparotomy; perforation.